Assessing the need for blockchain applications - Zwart, Nikolet (Technical Centre for Agricultural and Rural Cooperation, 2018)
Using the Oxford Blockchain Strategy Framework, Nikolet Zwart has analysed a use case of adding value through the local processing of food by multinational agribusinesses to illustrate the usefulness of any kind of blockchain analysis.